(3cJGH GdSGYIs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh HcQ eMeO Hf RcQjG bGd cfJ YfO GdhRjQ aNQi ai MUQ TF ef GdWH hHMVQJg LeGYg eef jOYjgG aJcde cd hGMO efge HbOQ eG HdZI Ydeg s
(3BNQgG (B:s
(3jOb hjfMd hjYLf hjMHH GdTQHg efg hRf OQge OQgejf hfUa HeGA MGQ fGaY EfTGA Gddg JYGdi JeJ GdcJGH GdSGYi ai GdWH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP (B- (3YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdWHs